2013
DOI: 10.1152/ajpendo.00398.2012
|View full text |Cite
|
Sign up to set email alerts
|

NOX2 deficiency attenuates markers of adiposopathy and brain injury induced by high-fat diet

Abstract: Pepping JK, Freeman LR, Gupta S, Keller JN, Bruce-Keller AJ. NOX2 deficiency attenuates markers of adiposopathy and brain injury induced by high-fat diet. Am J Physiol Endocrinol Metab 304: E392-E404, 2013. First published December 11, 2012 doi:10.1152/ajpendo.00398.2012.-The consumption of high-fat/ calorie diets in modern societies is likely a major contributor to the obesity epidemic, which can increase the prevalence of cancer, cardiovascular disease, and neurological impairment. Obesity may precipitate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
67
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(73 citation statements)
references
References 98 publications
(153 reference statements)
5
67
1
Order By: Relevance
“…The alteration in adipose tissue was depot specific, as we found no genotypeassociated differences in subcutaneous adipose mass; however, and strikingly, NOX2-KO mice did not gain nearly as much epididymal adipose mass as WT mice when challenged with a HF diet. This feature was also observed by Pepping et al (38), but, unlike their findings, the adipocytes of the NOX2-KO mice studied in our study were able to increase their size in response to overnutrition. Moreover, their leptin production was not altered.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The alteration in adipose tissue was depot specific, as we found no genotypeassociated differences in subcutaneous adipose mass; however, and strikingly, NOX2-KO mice did not gain nearly as much epididymal adipose mass as WT mice when challenged with a HF diet. This feature was also observed by Pepping et al (38), but, unlike their findings, the adipocytes of the NOX2-KO mice studied in our study were able to increase their size in response to overnutrition. Moreover, their leptin production was not altered.…”
Section: Discussionsupporting
confidence: 89%
“…Consistent with our finding, Lee et al (30) found increased inflammation and tissue infiltration of immune cells in NOX2-KO mice compared with WT mice during the development of arthritis. Moreover, Pepping et al found increased macrophage infiltration into EWAT of HF-fed WT mice, but not NOX2-KO mice (38), whereas we found a trend for increased EWAT macrophage infiltration in both chow-and HF-fed NOX2-KO mice compared with WT mice. On the other hand, You et al observed decreased kidney macrophage infiltration in NOX2-KO mice in a model of type 1 diabetes (50) attributed to lower levels of kidney Ccl2 (monocyte chemoattractant protein-1/MCP-1).…”
Section: Discussioncontrasting
confidence: 73%
See 1 more Smart Citation
“…3B). A recent report showed that Nox2-KO mice fed high fat diet had smaller visceral adipose deposits, attenuated visceral adipocyte hypertrophy, and diminished visceral adipose macrophage infiltration (31). We are currently assessing fat cells to determine further the impact of Nox2 on fat metabolism and oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…The tissues were washed with PBS for three times, incubated with anti-Iba1 antibody at 4 C overnight for activated macrophage labeling [7]. After PBS wash, tissues were incubated with biotinylated secondary antibody and ABC reagent according to manufacturer's manuals (Vector Laboratories, cat.…”
Section: 3'-diaminobenzidine (Dab) Staining and Cell Countingmentioning
confidence: 99%